Mathematical Problem Posing 2015
DOI: 10.1007/978-1-4614-6258-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Problem-Posing Research in Mathematics Education: Some Answered and Unanswered Questions

Abstract: This chapter synthesizes the current state of knowledge in problemposing research and suggests questions and directions for future study. We discuss ten questions representing rich areas for problem-posing research: (a) Why is problem posing important in school mathematics? (b) Are teachers and students capable of posing important mathematical problems? (c) Can students and teachers be effectively trained to pose high-quality problems? (d) What do we know about the cognitive processes of problem posing? (e) Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 62 publications
3
85
0
10
Order By: Relevance
“…The requirement to consider teachers is grounded on a growing body of research which has acknowledged problem posing as a valuable tool in developing mathematics teaching at all levels (e.g. Pittalis et al, 2004;Cai et al, 2015;Ellerton, 2015). Ticha and Hospesova (2013) found that prospective primary teachers acquired a deeper conceptual understanding of fractions.…”
Section: Potential Limitations To Mathematical Problem Posing In the mentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement to consider teachers is grounded on a growing body of research which has acknowledged problem posing as a valuable tool in developing mathematics teaching at all levels (e.g. Pittalis et al, 2004;Cai et al, 2015;Ellerton, 2015). Ticha and Hospesova (2013) found that prospective primary teachers acquired a deeper conceptual understanding of fractions.…”
Section: Potential Limitations To Mathematical Problem Posing In the mentioning
confidence: 99%
“…Problem posing is considered by many stakeholders as a pedagogy that can augment the learning and teaching of mathematics (e.g. Cai et al, 2015;Singer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to realize that some of these questions are among the unanswered questions proposed and analyzed by Cai et al (2015) in Chap. 1 of the book Mathematical Problem Posing (Singer et al 2015).…”
Section: A Retrospective Lookmentioning
confidence: 99%
“…Proposing a problem can be useful in bringing together a number of learning goals, both in group and individual learning setting. Furthermore, Cai, Hwang, Jiang, & Silber (2015) posit that problem-posing activities can improve students' learning achievement, reasoning and communication skills, and capture their motivation.…”
Section: Introductionmentioning
confidence: 99%